2007
DOI: 10.1007/s11695-007-9104-4
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up of Roux-en-Y Gastric Bypass Patients at 5 or more Years Postoperatively

Abstract: Long-term follow-up (5 to 9 years) after the RYGBP was associated with satisfactory mantainance of EWL, and resolution or improvement of the main co-morbidities was observed in the majority of the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
39
1
10

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 35 publications
8
39
1
10
Order By: Relevance
“…In the present study, the postoperative BMI ranged from 29.4 ± 5.6 to 31.6 ± 4.3 Kg/m² and the percentage of EBWL varied from 81.7 ± 21.4% to 72.2 ± 14.2%, proportional to the postoperative period; however, no statistical differences were found among the postoperative groups. Similar find ings were obtained by SEARS et al after 1 year of RYGBP in 75 patients with BMIs of 32.3 ± 8.6, and by Pajecki et al, who followed RYGBP patients for five to nine years and observed PEP% 2 years after surgery of 80.2% (BMI 29.3 ± 6.8) that decreased to 71.81% (BMI 35.5 ± 10) 5 years after surgery (18,22) . Our findings showed a decrease in the proportion of a tendency for diabetes resolution over the long term.…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, the postoperative BMI ranged from 29.4 ± 5.6 to 31.6 ± 4.3 Kg/m² and the percentage of EBWL varied from 81.7 ± 21.4% to 72.2 ± 14.2%, proportional to the postoperative period; however, no statistical differences were found among the postoperative groups. Similar find ings were obtained by SEARS et al after 1 year of RYGBP in 75 patients with BMIs of 32.3 ± 8.6, and by Pajecki et al, who followed RYGBP patients for five to nine years and observed PEP% 2 years after surgery of 80.2% (BMI 29.3 ± 6.8) that decreased to 71.81% (BMI 35.5 ± 10) 5 years after surgery (18,22) . Our findings showed a decrease in the proportion of a tendency for diabetes resolution over the long term.…”
Section: Discussionsupporting
confidence: 86%
“…According to most studies, hypertension control appears to be so linked to improvement on insulin sensitivity and proinflammatory state as to proper weight loss (11,15,16,27) . Previous Brazilian reports have shown similar results (9,21) .…”
Section: Discussionsupporting
confidence: 78%
“…[26][27][28]47,48 Partial or complete improvement was shown within 12 months after undergoing bariatric surgery, especially among the patients who had undergone gastric bypass, 10,47 thus reducing the need for antihypertensive drugs. 49,50 It seems again that our results were somehow related to the technique used for the majority of our patients, i.e. gastric bypass.…”
Section: Antihypertensive Drugsmentioning
confidence: 77%